Structural and Functional Alterations in Betel-Quid Chewers: A Systematic Review of Neuroimaging Findings - Sariah, Adellah; Liu, Zhening; Pu, Weidan; Liu, Haihong; Xue, Zhimin; Huang, Xiaojun (Frontiers in Psychiatry, 2019)
Background: A number of neuroimaging studies have investigated structural, metabolic, and functional connectivity changes in betel quid (BQ) chewers. We present a systematic review of neuroimaging studies with emphasis on key brain systems affected by BQ chewing to bring a better understanding on the neuro mechanisms involved in BQD. Methods: All BQ neuroimaging studies were identified by searching PubMed, EMBASE, and Google scholar for English articles published until March 2018 using the key words: Betel-quid, resting state, functional MRI, structural MRI, diffusion tensor imaging (DTI), and betel quid dependence basing on the PRISMA criteria. We also sought unpublished studies, and the rest were obtained from reference lists of the retrieved articles. All neuroimaging studies investigating brain structural, and functional alterations related to BQ chewing and BQ dependence were included. Our systematic review registration number is CRD42018092669. Results: A review of 12 studies showed that several systems in the brain of BQ chewers exhibited structural, metabolic, and functional alterations. BQ chewing was associated with alterations in the reward [areas in the midbrain, and prefrontal cortex (PFC)], impulsivity (anterior cingulate cortex, PFC) and cognitive (PFC, the default mode, frontotemporal, frontoparietal, occipital/temporal, occipital/parietal, temporal/limbic networks, hippocampal/hypothalamus, and the cerebellum) systems in the brain. BQ duration and severity of betel quid dependence were associated with majority of alterations in BQ chewers. Conclusion: Betel quid chewing is associated with brain alterations in structure, metabolism and function in the cognitive, reward, and impulsivity circuits which are greatly influenced by duration and severity of betel quid dependence.